2021
DOI: 10.24272/j.issn.2095-8137.2021.189
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide scan for selective footprints and genes related to cold tolerance in Chantecler chickens

et al.

Abstract: The Chantecler chicken, a unique Canadian indigenous breed, is well adapted to extremely cold environments. However, its genetic characteristics have not been well studied. Here, we analyzed the whole genomes of 10 Chantecler chickens and 121 worldwide chickens, which indicated that Chantecler chickens were derived from commercial chickens and exhibit a high level of inbreeding. Based on a genome-wide scan, we identified two vital candidate regions containing ME3 and ZNF536 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 64 publications
(91 reference statements)
3
16
0
Order By: Relevance
“…Knowledge about the patterns of LD decay can provide important insights into population history, demographic processes and breeding systems [ 68 , 69 ]. The LD estimates decreased with increasing genomic distance of SNP pairs, which was consistent with previous studies in chicken and livestock animals [ 70 , 71 ]. We found that all of the studied indigenous ecotypes followed the same pattern of decrease in LD as the genomic distance increased, however more rapid decrease in LD over increasing genomic distance was observed in White leghorn chickens (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Knowledge about the patterns of LD decay can provide important insights into population history, demographic processes and breeding systems [ 68 , 69 ]. The LD estimates decreased with increasing genomic distance of SNP pairs, which was consistent with previous studies in chicken and livestock animals [ 70 , 71 ]. We found that all of the studied indigenous ecotypes followed the same pattern of decrease in LD as the genomic distance increased, however more rapid decrease in LD over increasing genomic distance was observed in White leghorn chickens (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The r 2 values obtained in this study for native ecotypes were in the ranges of 0.52 to 0.57 at marker pairs distance of 100 Kb, which agreed with those reported for Chinese and Canadian native chicken populations [ 70 , 72 ]. We further found a markedly higher level of LD across all genomic distances in White Leghorn chickens followed by Arian group (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…SAMM had a highest linkage disequilibrium level, followed by Chinese Merino and Australian Merino (Figure S1). These results were consistent with the observations in other domestic animals including dogs (Gou et al, 2015), pigs (Muñoz et al, 2019), chickens (Wang et al, 2021;Xu et al, 2021), and ducks (Guo et al, 2021), indicating that domestication and artificial selection induced a loss of genetic diversity and an increase of inbreeding.…”
Section: Introductionsupporting
confidence: 90%
“…2 b and Additional file 4: Fig. S1b), indicating potential risks of their extinction following inbreeding depression and thus calling for conservation measures [ 31 , 46 ].
Fig.
…”
Section: Utility and Discussionmentioning
confidence: 99%
“…The ROH (Runs of homozygosity) of each group was calculated with PLINK parameters “–homozyg-window-snp 50 –homozyg-snp 50 –homozyg-kb 500 –homozyg-density 50 –homozyg-window-missing 5 –homozyg-window-threshold 0.05 –homozyg-window-het 3”. We then calculated genomic inbreeding coefficients ( F ROH ) by the formula: F ROH = L ROH /L total [ 30 , 31 ]. To avoid the bias due to sample size variation, we reduced the sample size of each group down to five, following random sampling 10 times, then compared with the calculation results of the original samples.…”
Section: Construction and Contentmentioning
confidence: 99%